1982
DOI: 10.1136/pgmj.58.676.80
|View full text |Cite
|
Sign up to set email alerts
|

The clinical course of acute type A hepatitis in chronic HBsAg carriers—a report of 3 cases

Abstract: The clinical, virological, and biochemical course of 3 chronic HBsAg carriers who developed acute hepatitis A is described. Two of the patients had pre-existent chronic active hepatitis. The clinical course in each case was benign with resolution within one month, and there was a marked fall in HBsAg titre in one of the patients with chronic active hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0
1

Year Published

1984
1984
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 10 publications
3
13
0
1
Order By: Relevance
“…Our results confirm previous findings that acute HAV infection does not cause severe liver injury in patients with chronic HBV infection, [16][17][18][19][20] but they differ from the findings of other large series. 2 It is not easy to reconcile such differences; however, in other studies, most HBV-infected patients with fulminant hepatitis A had cirrhosis, the role of HCV was not evaluated, and the possibility of coinfections with HBV and HCV could not be ruled out.…”
Section: Discussionsupporting
confidence: 76%
“…Our results confirm previous findings that acute HAV infection does not cause severe liver injury in patients with chronic HBV infection, [16][17][18][19][20] but they differ from the findings of other large series. 2 It is not easy to reconcile such differences; however, in other studies, most HBV-infected patients with fulminant hepatitis A had cirrhosis, the role of HCV was not evaluated, and the possibility of coinfections with HBV and HCV could not be ruled out.…”
Section: Discussionsupporting
confidence: 76%
“…Viola e cols. 20 e Zachoval e cols. 21 não encontraram diferenças nos níveis de bilirrubina, transaminases e nem na evolução de pacientes portadores crônicos do vírus B, com infecção aguda por HVA.…”
Section: Discussionunclassified
“…Other papers refer to the course of acute HA in groups of institutionalized persons with past contact with HBV as being either milder [6] or aggravated [7]. More recently it has been concluded that HAV superinfection in HBsAg carriers neither causes a more severe illness, nor affects the course of chronic HB [8][9][10].…”
Section: Introductionmentioning
confidence: 99%